Drug-Induced Bullous Sweet Syndrome with Multiple Autoimmune Features. (12th August 2010) - Lund, Jared J.; Stratman, Erik J.; Jose, Deepa; Xia, Ling; Wilson, Deborah; Moizuddin, Mohammed
Abstract : Sweet syndrome (SS) (Acute Febrile Neutrophilic Dermatosis) has been reported in association with autoimmune phenomena including relapsing polychondritis, drug-induced lupus, and the development of antineutrophil cytoplasmic antibodies (ANCAs). However, a combination of these autoimmune features has not been reported. Herein, we report a case of drug-induced bullous SS with ocular and mucosal involvement, glomerulonephritis, and multiple autoimmune features including clinical polychondritis with antitype II collagen antibodies, ANCAs, antinuclear (HEp-2), and antihistone antibodies in a patient on hydralazine and carbamazepine.